Guest Editors' Introduction. Issue 2 (2nd April 2016) - Le Roy, Frédéric; Dagnino, Giovanni Battista; Czakon, Wojciech
Abstract: This editorial introduces the papers presented in the special issue. In a first point we show the coopetition research rise. Coopetition research really begins with the 21th century. Since the first academic papers on coopetition there is a fast growing trend which is looked as an opportunity for publications. Researches are now specialized in narrow topics, as the link between coopetition and innovation. The second point of this editorial introduces the main elements of the discussion on this topic. The link between coopetition and innovation is driven by "coopetitive dilemma" as a paradox between the need of cooperation to create value, and the attraction to compete for value appropriation. Coopetition should be a real opportunity to develop innovation, but also creates a risk of knowledge transfer to the coopetitors. So cooperating with competitor for innovation is a strategy under tension in a situation of instable equilibrium. The question is to know if firms must or not follow this kind of strategy. The question is also to know if risk created by coopetition for innovation could be successfully managed. Papers presented in this special issue are dedicated to these questions.